ANALISIS PENENTUAN PERSEDIAAN BAHAN BAKU YANG OPTIMAL DI PT DJTOE MESINDO BATAM - Saprianto, Tono; Hazimah, Hazimah (Computer Science and Industrial Engineering, 2021)
This journal emphasizes on the analysis of determination of optimum raw material in PT Xyz. The high raw material inventory allows the company to be flexible in fulfilling sudden product orders. However, this way results an inefficient coslt. Therefore, inventory control is one of the important working capital in a company. One of that company is PT. Xyz. It is a company located in the Tanjung Uncang Batam area. This company is engaged in manufacturing the electric engine. The needs that meet local and international market, in order for the production process to run optimally, the company must provide quality raw materials. The researcher employs quantitative descriptive method in this journal. Research variables in this journal are calculating the required sphere, ordering costs, storage costs and waiting time. Furthermore, data collection techniques in this journal are observation, interviews, and documentation. Moreover, to analyze determination of optimum raw material in PT Xyz, the research uses EOQ (Economic Order Quantity) method. This method employed in this journal because it serves to protect and guard against possible shortages of raw materials, so as not to become an obstacle in the production process. From the analysis, the method of EOQ was used made inventory of raw material so efficient and the company also could save cost more than was used company policy for raw material